Community health workers for pandemic response: a rapid evidence synthesis. Issue 6 (10th June 2020) - Bhaumik, Soumyadeep; Moola, Sandeep; Tyagi, Jyoti; Nambiar, Devaki; Kakoti, Misimi
Abstract : Introduction: Coronavirus disease (COVID-19), affects 213 countries or territories globally. We received a request from National Health Systems Resource Centre, a public agency in India, to conduct rapid evidence synthesis (RES) on community health workers (CHWs) for COVID-19 prevention and control in 3 days. Methods: We searched PubMed, websites of ministries (n=3), public agencies (n=6), multilateral institutions (n=3), COVID-19 resource aggregators (n=5) and preprints (n=1) (without language restrictions) for articles on CHWs in pandemics. Two reviewers screened the records independently with a third reviewer resolving disagreements. One reviewer extracted data with another reviewer cross-checking it. A framework on CHW performance in primary healthcare not specific to pandemic was used to guide data extraction and narrative analysis. Results: We retrieved 211 records and finally included 36 articles. Most of the evidence was from low-and middle-income countries with well-established CHW programmes. Evidence from CHW programmes initiated during pandemics and for CHW involvement in pandemic response in high-income countries was scant. CHW roles and tasks change substantially during pandemics. Clear guidance, training for changed roles and definition of what constitutes essential activities (ie, those that must to be sustained) is required. Most common additional activities during pandemics were community awareness, engagement and sensitisation (including for countering stigma) and contact tracing. CHWs were reported to be involved in all aspects of contact tracing - this was reported to affect routine service delivery. CHWs have often been stigmatised or been socially ostracised during pandemics. Providing PPE, housing allowance, equal training opportunities, transportation allowance, improving salaries (paid on time and for a broad range of services) and awards in high-profile public events contributed to better recruitment and retention. We also created inventories of resources with guiding notes on guidelines for health workers (n=24), self-isolation in the community (n=10) and information, education and counselling materials on COVID-19 (n=16). Conclusions: CHWs play a critical role in pandemics. It is important to ensure role clarity, training, supportive supervision, as well as their work satisfaction, health and well-being. More implementation research on CHWs in pandemics is required.